(untitled) (Journal of University of Babylon for Engineering Sciences, 2023)
The urban fabric in historical cities faces enormous challenges in the field of urban conservation and reconstruction, due to the authenticity of its elements and components with multiple values ​​that are irreplaceable in the event of their disappearance. The diversity of urban conservation methods and trends makes adopting one of them a challenge in addition to the compound damage caused by disasters, which requires experts to conduct focused analyzes of the reality of the urban heritage in comparison with the available capabilities, whether economic, social or other. The integrative conservation approach represents one of the trends followed globally in the field of urban conservation, but the absence of previous studies that show and classify its criteria and indicators increases the difficulty of adopting it as a trend for urban conservation in historical cities. The current research aims to identify and define the requirements and limitations of the integrative Conservation approach and define its aspects and standards, with the aim of employing them and their indicators as guidelines and directives to develop a plan for the reconstruction of the historical urban fabric. The research adopted the approach of comparative analysis of conservation trends and intervention mechanisms and analysis of the relevant charters to reach the standards of integrative conservation, and then an analysis of a number of international experiences that adopted this approach as a case study to show the extent to which they achieve these standards. The research found a set of criteria for integrative conservation and its effective social, functional and visual indicators, which can be employed as instructions and guidelines within plans and scenarios for the reconstruction and conservation of historical cities.